Tradisi Intelektual Islam pada Masa Abbasiyah dan Relevansinya terhadap Pengembangan Pendidikan Islam Kontemporer - Zen Magata Larashati; Kholid Mawardi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The Islamic intellectual tradition during the Abbasid Dynasty constituted one of the most significant foundations for the development of Islamic civilization and the advancement of global knowledge. This study aims to analyze the characteristics of the Islamic intellectual tradition during the Abbasid period, the factors that supported its development, and its relevance to the advancement of contemporary Islamic education. This research employs a library research method with a descriptive qualitative approach through the analysis of various relevant scholarly sources. The findings reveal that the Abbasid intellectual tradition was characterized by strong state support for the advancement of knowledge, openness to diverse global intellectual traditions, the development of educational institutions and centers of learning such as Bayt al-Hikmah, the emergence of a robust academic culture, and the integration of knowledge with ethical and moral values (adab). The growth of this intellectual tradition was supported by political stability, economic prosperity, translation movements of foreign works, and the cosmopolitan nature of society. The Abbasid intellectual tradition remains highly relevant to contemporary Islamic education, particularly in addressing the dichotomy between religious and secular sciences, enhancing literacy and research culture, strengthening academic integrity, and promoting education oriented toward both character formation and scientific mastery. Therefore, the values cultivated during the Abbasid era can serve as a foundation for developing an integrative, innovative, and adaptive Islamic educational system that responds to technological advancements while maintaining Islamic principles.   Keywords: Islamic Intellectual Tradition, Abbasid Dynasty, Contemporary Islamic Education